2018
DOI: 10.1021/acs.jpcc.8b00717
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the Ni–Ni Bonding Strength in Metal-String Complexes Using Head-to-Head Nanorods and Electrochemical Surface-Enhanced Raman Spectroscopy

Abstract: We report the bonding strength of nickel ions in trinickel extended metal atom chains (EMACs) and dinickel complexes using Raman, surface-enhanced Raman scattering (SERS), and electrochemical SERS (ECSERS). By using the redox ability of gold and silver nanoparticles during plasmonic excitation, the bonding strength and the valence state of metal ions can be determined. For dinickel complexes, we assign the Raman band at 322 cm–1 to Ni2+–Ni3+ stretch in [Ni2(TPG)4]­BF4 (TPG = N,N′,N″-triphenylguanidinate, [Ni2]… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…For rods of size 12.1 ± 0.7 × 29.4 ± 2.7 nm 2 aspect ratio 2.4 ± 0.2, the longitudinal plasmonic mode lies at 627 nm and is red-shifted to 772 nm when connected by complexes. Long chains are depicted in the SEM images; the complexes anchor on both ends of the AuNRs by chlorides in solution, forming head-to-head chains. , Ying et al reported that metallaynes with sulfide moieties can serve as connectors for gold nanoparticle assemblies . Orendorff and Murphy reported that AuNR has {110}/{100} facets on the sides and {100}/{111}­on the heads, and the bridging molecules mostly anchor on the {111} facets .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…For rods of size 12.1 ± 0.7 × 29.4 ± 2.7 nm 2 aspect ratio 2.4 ± 0.2, the longitudinal plasmonic mode lies at 627 nm and is red-shifted to 772 nm when connected by complexes. Long chains are depicted in the SEM images; the complexes anchor on both ends of the AuNRs by chlorides in solution, forming head-to-head chains. , Ying et al reported that metallaynes with sulfide moieties can serve as connectors for gold nanoparticle assemblies . Orendorff and Murphy reported that AuNR has {110}/{100} facets on the sides and {100}/{111}­on the heads, and the bridging molecules mostly anchor on the {111} facets .…”
Section: Resultsmentioning
confidence: 99%
“…The absorption during the redox processes can be recorded in situ to assist in assigning the electronic structures. 19,20 Diruthenium possesses high polarizability; thus, intense Raman signal is expected. This provides SERS detection with great sensitivity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Wu et al employed an electrochemical surface-enhanced Raman scattering (ECSERS) technique and assigned a new band at 350 cm –1 , appearing from oxidation of Ni 3 (dpa) 4 Cl 2 under applied voltages, to the symmetric stretching mode of Ni 3 υ Ni 3 ,sym of the [Ni 3 ] 7+ core. In addition, the reduction potential of Ni 3 (dpa) 4 X 2 is smaller than the oxidation potential of gold nanoparticles (AuNPs); , the complex was reduced to [Ni 3 ] 5+ when simply attached to gold nanoparticles.…”
Section: Introductionmentioning
confidence: 99%
“…Likewise, Kitagawa et al 23 examined the exchange constants, electronic structures, magnetic properties, and electron conductivities of Ni 5 (tdpa) 4 Cl 2 (tdpa = tripyridyldiamido) and Ni 7 (teptra) 4 Cl 2 (teptra = tetrapyridyltriamido) with the B3LYP functional. Wu et al 24 employed an electrochemical surface-enhanced Raman scattering (ECSERS) technique and assigned a new band at 350 cm −1 , appearing from oxidation of Ni 3 (dpa) 4 Cl 2 under applied voltages, to the symmetric stretching mode of Ni 3 υ Ni 3 ,sym of the [Ni 3 ] 7+ core. In addition, the reduction potential of Ni 3 (dpa) 4 X 2 is smaller than the oxidation potential of gold nanoparticles (AuNPs); 18,25 the complex was reduced to [Ni 3 ] 5+ when simply attached to gold nanoparticles.…”
Section: Introductionmentioning
confidence: 99%